Pharmacokinetics of Asciminib in Individuals With Hepatic or Renal Impairment. (16th July 2021) - Hoch, Matthias; Sato, Masahiko; Zack, Julia; Quinlan, Michelle; Sengupta, Tirtha; Allepuz, Alex; Aimone, Paola; Hourcade‐Potelleret, Florence
Abstract: Asciminib is an investigational, first‐in‐class, specifically targeting the ABL myristoyl pocket (STAMP) inhibitor of BCR‐ABL1 with a new mechanism of action compared with approved ATP‐competitive tyrosine kinase inhibitors. This report describes the findings from 2 phase 1 studies assessing the pharmacokinetic (PK) profile of a single dose of asciminib (40 mg) in individuals with impaired renal function (based on absolute glomerular filtration rate; NCT03605277) or impaired hepatic function (based on Child‐Pugh classification; NCT02857868). Individuals with severe renal impairment exhibited 49%‐56% higher exposure (area under the curve [AUC]), with similar maximum plasma concentration (Cmax ), than matched healthy controls. Based on these findings, as per the protocol, the PK of asciminib in individuals with mild or moderate renal impairment was not assessed. In individuals with mild and severe hepatic impairment, asciminib AUC was 21%‐22% and 55%‐66% higher, respectively, and Cmax was 26% and 29% higher, respectively, compared with individuals with normal hepatic function. Individuals with moderate hepatic impairment had similar asciminib AUC and Cmax than matched healthy controls. The increase in asciminib AUC and Cmax in the mild hepatic impairment cohort was mainly driven by 1 participant with particularly high exposure. Asciminib was generally well tolerated, and the safety data were consistent with its known safety profile. In summary, these findings indicate that renal or hepatic impairment has no clinically meaningful effect on the exposure or safety profile of asciminib, and support its use in patients with varying degrees of renal or hepatic dysfunction.